2013
DOI: 10.1371/journal.pone.0065379
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Bacterial Activity of Recombinant Human β-Defensin-3 Secreted in the Milk of Transgenic Goats Produced by Somatic Cell Nuclear Transfer

Abstract: The present study was conducted to determine whether recombinant human β-defensin-3 (rHBD3) in the milk of transgenic goats has an anti-bacterial activity against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus) and Streptococcus agalactiae (S. agalactiae) that could cause mastitis. A HBD3 mammary-specific expression vector was transfected by electroporation into goat fetal fibroblasts which were used to produce fourteen healthy transgenic goats by somatic cell nuclear transfer. The expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In the present study, IVF embryos were used as a control for the identification of specific responses of the uterine DBA + leukocytes derived from non-pregnant endometrium to SCNT embryos. The IVF protocol used in this study had been previously shown to produce fetuses that are not different from in vivo -derived fetuses in growth and endocrine parameters [ 18 ]. DBA lectin reactivity has been widely used for histological recognition and isolation of uterine NK cells in pregnant mice [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, IVF embryos were used as a control for the identification of specific responses of the uterine DBA + leukocytes derived from non-pregnant endometrium to SCNT embryos. The IVF protocol used in this study had been previously shown to produce fetuses that are not different from in vivo -derived fetuses in growth and endocrine parameters [ 18 ]. DBA lectin reactivity has been widely used for histological recognition and isolation of uterine NK cells in pregnant mice [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the targeting of COL1A1 in sheep (McCreath et al, 2000), somatic cell nuclear transfer technology has provided an alternative means of cell-mediated transgenesis to circumvent the requirement for embryonic stem cells to generate gene-targeted animals such as sheep (Denning et al, 2001), cattle (Kuroiwa et al, 2009), goat (Liu et al, 2013), and pigs (Dai et al, 2002;Lai et al, 2002). It is technically challenging to produce gene-targeted cell lines as donors with sufficient genetic stability for somatic cell nuclear transfer.…”
Section: Discussionmentioning
confidence: 99%
“…The SCNT procedure was conducted as described previously . Briefly, the polar body and metaphase plate were sucked out, and a single round donor cell was injected into the perivitelline space of the enucleated oocytes.…”
Section: Methodsmentioning
confidence: 99%